Torsion of normal adnexa in a 31-year-old woman: A case report and literature review - Nao Wakui; Ai Miyoshi; Yuji Kamei; Takeya Hara; Akiko Fujishiro; Serika Kanao; Hirokazu Naoi; Hirohumi Otsuka; Masaaki Nagamatsu; Takeshi Yokoi (Wolters Kluwer Medknow Publications, 2018)
It is known that a large ovarian cyst will likely cause torsion. However, normal adnexal torsion is rare and occurs in premenarchal girls in most cases. This is a case of a reproductive woman. A 31-year-old woman suffering from acute abdominal pain in the lower and right side consulted her gynecologist. The next day she had a computed tomography performed and was suspected of ovarian torsion. She did not have fever, nausea, or leukocytosis, but her abdominal pain persisted. Diagnostic laparoscopy was performed and showed torsion of the right fallopian tube, which was swollen and looked like a hydrosalpinx with a normal ovary. We did detorsion and excision of the right tube. However, pathological findings showed that the right tube was not a hydrosalpinx but was swollen due to blood stasis. We determined that this case was torsion of normal adnexa. In such cases, diagnostic laparoscopy is very effective.